ANALISIS KAMPANYE KOMERSIAL MEDIA SOSIAL SEBAGAI MEDIA PROMOSI DALAM MENDUKUNG PERKEMBANGAN BISNIS UMKM INDONESIA - Sao, Wilhelmina (Universitas 17 Agustus 1945 Surabaya, 2025)
In the current technological era, it is certainly an advantage for the community in their daily activities. Today's technological advances are considered to be able to reduce the burden of community activities because the technology is considered to have created many updates for more effective and efficient community activities, especially for Indonesian MSMEs, which with the presence of their businesses can help raise the economic level in Indonesia. In addition, social media today is considered to be included in the category of commercial campaigns because the attention given from social media users to a product marketed by MSMEs through social media provides significant benefits, one of which can be felt in Eat Sambal MSME products that we often encounter in the TikTok application. This research uses the Descriptive Qualitative method presented in the Research Methods subchapter. This research was conducted through a benchmark experiment to describe the urgency of the importance of social media promotion media in collaboration with local MSMEs. This research also tries to conduct an in-depth description of the utilization of social media in the business sector that social media has various advantages if a user can utilize social media properly according to its function. The findings that were successfully found in this study are in the form of advertisements that can affect people's purchasing power due to an interest that people have in these advertisements. Commercial promotions can also have a good and broad impact on every social media user. The main objective of this research is that apart from being able to utilize social media as a promotional tool, Indonesian MSME activists must also be able to control and present good and correct promotions in accordance with policies and regulations related to society. Keywords: MSMEs, Promotion, Social Media, Eat Sambal